The Effect of the Cooperative Learning Model in Improving the Ability to Recognize Number Symbols for Students with Intellectual Disability - Vivin Andriani; Grahita Kusumastuti (Universitas Muhammadiyah Enrekang, 2022)
A number symbol is a symbol that expresses an amount using numbers. a number symbol is a value that is an abstract or symbol of a number to determine an amount as an enumeration or measurement. Introducing this symbol of numbers to children with mild mental disabilities is not in an easy way, because this mildly impaired child has an IQ below average, therefore teachers must be patient and the learning media used by teachers is also creative and innovative so that children with mental disabilities are not bored and understand during learning. Therefore, this study will examine the influence of the horay course review (CRH) type cooperative learning model can improve the ability to recognize the number symbol one to five for children with mild mental impairment. This type of research is experimental research with a single subject or Single Subject Research (SSR), designed A-B-A. This study was conducted using a Creative Learning model of the Course Review Horay (CRH) type as a free variable, and related variables in the form of recognizing the symbol of numbers one to five. This study uses analysis in conditions and between conditions which can be described in benthic tables and figures. The results of this study can be proven from the tendency to stability at the mean level A1, which is 0%. Then there was an increase when given an intervention (B) where the mean level was 49% and after being given the intervention, namely the condition A2 mean level was 72%. So it can be concluded that there is an increase in each condition which means that the child is able to recognize the symbol of the numbers one to five.